PENGARUH KOMUNIKASI, DISIPLIN KERJA DAN PENGAWASAN TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. KUNANGO JANTAN KABUPATEN KAMPAR - Rudiana, Titik; Sasmita, Jumiati; Marzolina, Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the influence of communication, work discipline and supervision of employee spirit. As for the population in this study are all employees of PT Kunango Jantan Kampar with the number of 153 people. Sampling is done by accidental method and the determination of the number of samples is done by using Slovin formula. Analysis of data used is multiple linear regression with the help of SPSS program version 18.00. From the test result that has been done, simultaneous test (F-test) shows that Communication, work discipline and pengawasaan simultaneously affect to employee morale, while partial test (T-test) indicate that Communication, work discipline and partial pengawasaan effect Employee morale. To maximize employee morale, the company should provide an opportunity for employees to participate in efforts to advance the company and to maximize employee communication, expected to the company to establish decision-making based on information that takes into account the situation and conditions that exist.Keywords : Communication, Work Discipline, Supervision and Employee Spirit